Kauman Kampung Qur’an Sebagai Kawasan Wisata Edukasi Religius Di Kota Semarang - Rina Kurniati; Kartika Yuliani (Ruang, 2017)
Kauman is a historic kampung in Semarang and historically inhabited by the Java community is Muslim. Characteristic of Kauman with the number of ‘santri’ as the center of Semarang in the past. Mosque Kauman Semarang as a center of Islamic religion also has an important role in the development of Semarang until now. Kauman main characteristic is their guardian mosque, circle the square, the center of government, and traditional markets. Kauman as a center of Islamic culture, the Great Mosque Kauman as a relic Ki Ageng Pandan Arang is the oldest mosque in Semarang. The tradition of religion is ‘dugderan’ activities undertaken ahead of the month of Ramadhan to inform the public that tomorrow is already entered 1 Syawal or Ramadhan. This tradition is accompanied by a parade or procession through the main streets of the city of Semarang. Kauman progressing increasingly crowded, with many migrants who need land for dwelling and trade spaces. Therefore Kauman require conservation efforts to restore the identity of the region to invite people's maintaining a culture that still exists. The conservation efforts are implemented is still maintaining its culture. Meanwhile, to keep the buildings architectural style Arab efforts to support the preservation of the religious educational tourism branding "Kauman Kampung Qur'an".